Tradisi Ritual Nede Sebagai Media Meminta Hujan di Makam Embung Puntiq, Kecamatan Praya Timur Kabupaten Lombok Tengah (Religion, Culture, and State Journal, 2021)
This article examines the construction of the nede ritual tradition at the Embung Puntiq tomb as a medium for asking for rain. The nede ritual is one of the rituals carried out by the people of the Dusun Rentang every year. The tradition of nede ritual has an essential role in helping the people who live around the surrounding Dusun Rentang to convey their vows either in the form of asking for rain, healing from illness, or asking for something else. This study uses qualitative research methods in data collection and analysis. Determination of informants in this study was using purposive sampling. The data collection techniques used observation, interview, and documentation techniques. The collected data were analyzed and interpreted using the social construction theory of Peter L Berger and Thomas Luckman. This study indicates that the history of the emergence of the nede ritual, in general, began with a drought in the community and made the Embung Puntiq tomb a place for the nede ritual. The emergence of the history of the Embung Puntiq tomb stems from the war that occurred during the reign of Datu Pejanggik Raden Mas Panji Meraje Kusume, who was attacked by the Anak Agung Karang Asem, the Balinese kingdom that invaded the West part of Lombok Island. Raden Mas Panji Meraje Kusume fell when he drew his sword until he scratched his little finger and dripped blood on the spot. He then disappeared suddenly, and the place was planted with banana trees as a sign of his grave. The process and stages in implementing the nede ritual include determining the date on the 7th month, cooking offerings, and making other preparations. The nede ritual process starts from saying greetings, going around the tomb three times, reading the tomb's history, reading the sembek prayer, and finally eating together. The reason people still maintain the nede ritual tradition is because their beliefs and knowledge are so attached to God and the beliefs of their ancestors, which must be maintained and preserved from generation to generation.